16S rRNA deep sequencing identifies Actinotignum schaalii as the major component of a polymicrobial intra-abdominal infection and implicates a urinary source. (3rd May 2017) - Bryan, Andrew; Kirkpatrick, Lindsey M; Manaloor, John J; Salipante, Stephen J
Abstract : Introduction. It can be difficult to catalogue the individual organisms comprising polymicrobial patient infections, both because conventional clinical microbiological culture does not facilitate the isolation and enumeration of all members of a complex microbial community, and because fastidious organisms may be mixed with organisms that grow rapidly in vitro . Empiric antimicrobial treatment is frequently employed based on the anatomical site and the suspected source of the infection, especially when an appropriately collected surgical specimen is not obtained. Case presentation. We present a case of an intra-abdominal infection in a patient with complex anatomy and recurrent urinary tract infections. Imaging did not reveal a clear source of infection, no growth was obtained from urine cultures and initial abdominal fluid cultures were also negative. In contrast, 16S rRNA deep sequencing of abdominal fluid samples revealed mixed bacterial populations with abundant anaerobes, including Actinotignum schaalii ( Actinobaculum schaalii ). Ultimately, only Enterobacter cloacae complex and meticillin-resistant Staphylococcus aureus, both of which were identified by sequencing, were recovered by culture. Conclusion. The clinical application of 16S rRNA deep sequencing can more comprehensively and accurately define the organisms present in an individual patient's polymicrobial infection than conventional microbiological culture, detecting species that are not recovered under standard culture conditions or that are otherwise unexpected. These results can facilitate effective antimicrobial stewardship and help elucidate the possible origins of infections.